The Potential of Vernacular Materials to the Sustainable Building Design: Experience of Construction Design with Adobe Material - Kuyrukçu, Zafer; Kuyrukçu, Emine Yıldız (International Journal of Natural Sciences Research, 2015)
In order to achieve sustainable architecture, cultural and sustainable design principles should be considered in a complementary relationship. Sustainable design implies the recycling of energy, either by the use of passive energy or renewable energy. It also requires harmony with local economies and data supporting biological diversity. Adobe traditional building material which is a cheap, environmentally friendly and abundant and has been used extensively for construction around the world. For this purpose, this study promotes the use of adobe as a sustainable material. Also this study is aimed to evaluate the progress in designing skills of students by using adobe as a sustainable material in architectural design education with a studio sample. The architectural design practice and use of adobe were evaluated with all positive and negative aspects within the context of students projects. These studies provide an excellent contribution for the recognition of the advantages of adobe as a building material, encouraging its use in new architecture and architectural education.